2017
DOI: 10.1007/s00039-017-0402-2
|View full text |Cite
|
Sign up to set email alerts
|

Regularity of the optimal sets for some spectral functionals

Abstract: In this paper we study the regularity of the optimal sets for the shape optimization problemwhere λ 1 (·), . . . , λ k (·) denote the eigenvalues of the Dirichlet Laplacian and | · | the d-dimensional Lebesgue measure. We prove that the topological boundary of a minimizer Ω * k is composed of a relatively open regular part which is locally a graph of a C ∞ function and a closed singular part, which is empty if d < d * , contains at most a finite number of isolated points if d = d * and has Hausdorff dimension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(98 citation statements)
references
References 37 publications
2
95
0
Order By: Relevance
“…As mentioned above, a regularity result, for the optimal sets for the first eigenvalue of the Laplacian, was proved Briançon and Lamboley in [6]. The regularity of the optimal sets for more general spectral functionals was studied in [10], [34], [? ] and [?].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, a regularity result, for the optimal sets for the first eigenvalue of the Laplacian, was proved Briançon and Lamboley in [6]. The regularity of the optimal sets for more general spectral functionals was studied in [10], [34], [? ] and [?].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…for every d > d * (see also [34] for an argument using only the monotonicity of W ). Thus, as a consequence of Lemma 5.37, Lemma 5.38 and the results from [40] and [34], we get Appendix A. Extremality conditions and Lebesgue density…”
mentioning
confidence: 99%
“…In the last years, in the study of free boundary problems, it has been shown how to prove the same condition, in a weaker sense, without regularity assumptions. Two possible ways are to consider ∆u as a measure concentrated on the boundary (see [1]), or to use the viscosity solutions approach (see [18,37]). To start with, we prove that u is radially symmetric.…”
Section: Remark 214mentioning
confidence: 99%
“…Let r > 0, x 0 ∈ R 2 and u ∈ H 1 loc (R d ). The relation between W op and the excess E is given by the following formula, which holds for any function u and can be obtained by a direct computation (see [19] and [16]).…”
Section: 2mentioning
confidence: 99%
“…, n, is C 1,α regular (Theorem 1.8). This line of study has become increasingly important in recent years, where regularity results for solutions of free-boundary problems, and in particular almost-minimizers, have been applied to study the regularity of shape optimization problems involving eigenvalues of the Dirichlet-Laplacian (see for instance [16,14,15,9]).…”
Section: Introductionmentioning
confidence: 99%